The new development of plus size women body sizing for sportswear appearance / Nur Awatif Adawiyah Abdul Aziz and Shaliza Mohd Shariff - Abdul Aziz, Nur Awatif Adawiyah Abdul Aziz; Mohd Shariff, Shaliza (Universiti Teknologi MARA, 2020)
In this globalization era, the overall look of women's plus size sportswear is one of the issues that is still being faced by plus size ladies today. The sportswear that is produced today makes the plus size women feel excluded from society as they could not fit the current trend due to the body image that they owned. Plus size women usually faced a problem in choosing the right sports attire due to their varying sizes and body shapes. Plus size consists of 7 types of body shapes that have different widths on each part of their body. This group of people constantly faced similar problems in finding the best sportswear that suits their size as the current sports garment in the market does not get high demand in producing plus size workout garments which is much costly compared to the normal sports attire. The research aim is to create plus-size sportswear and the design criteria that could fit the seven types of plus size body shape On this basis, the innovation of plus size sportswear for plus size women will increase their selfconfidence, and the essentials factors of the design will give maximum usage to them which will give a good look to their physical appearance.